PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN BERBASIS ETNOMATEMATIKA PADA MATERI LINGKARAN KELAS VI DI SEKOLAH DASAR - Ratih Elvia Valda; Ni Luh Sakinah; Siti Mas’ula (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
The development in this article is designed to develop ethnomathematics-based learning video media that was valid and practical by expert lecturers and elementary school teachers. Malang’s culture is associated with ethnomathematics through learning videos including Keripik Tempe, Keramik Dinoyo, and Malang’s Monument Square, which was shaped as a circle. The three learning videos were classified based on the meaning and elements of the circle terms, the way to find out the extensive area and circumference of the circle, and the way to solve the mathematical problems of the circle learning material explained through ethnomathematics in Malang’s culture. The learning video began with the opening activity, telling the story of Malay cultural history, the relation to the circle learning material, and the closing activity accompanied by an evaluation in the form of providing question tests. The research and development model used was R2D2 (recursive, reflective, design and development). Based on the results of the media development and trials, it can be concluded that ethnomathematics-based learning video media on circle learning material for sixth-grade students was valid and practical to use in elementary schools as a learning medium.